Philosophies of Sex : Critical Essays on The Hermaphrodite - Bergland, Renee L., 1963-; Williams, Gary, 1947 May 6- (Book collections on Project MUSE., 2012)
"An introduction by Bergland and Williams traces the (re)discovery of Howe's manuscript and the beginnings of commentary as word spread about this remarkable text. Mary Grant, an early reader, invokes the excitement and frontier spirit of women's history in the 1970s. Marianne Noble and Laura Saltz place the narrative within the frames of European and American Romanticism and of Howe's other writings. Betsy Klimasmith, Williams, Bethany Schneider, and Joyce Warren explore connections between Howe's novel and other ground-breaking nineteenth-century works on gender, sexuality, and relationship. Bergland and Suzanne Ashworth explore The Hermaphrodite's suggestive invocations of two other kinds of "texts": sculpture and theology"--Publisher's description